Decision-Making of Electronic Commerce Supply Chain considering EW Service - Yuyan Wang; Zhaoqing Yu; Liang Shen; Runjie Fan (Complexity)
With the rapid development of the network economy, it is a marketing strategy to provide an extended warranty (EW) service. Considering the differences in the EW service providers and dominant enterprises, this paper proposes four kinds of decision-making models and aims to study decisions of the electronic commerce supply chain, including EW price, sales price, and service level of e-platform. Through comparative analysis and numerical analysis, this research shows that, among four decision-making models, the highest system profit can be achieved when the seller provides the EW service and the e-platform dominates the system. For electronic commerce supply chain enterprises, whether to dominate the system or to provide EW service, it is conducive to the increase of profits. When the e-platform provides the EW service, the conclusion is that who dominates the system is the one who gets more profit. However, when the seller provides the EW service, the conclusion is that who dominates the system is the one who gets less profit. When the EW service is offered by the dominating enterprise, service levels of the e-platform are lower.